Strengthening Hospital Competitiveness to Improve Patient Satisfaction and Better Health Outcomes 2019
DOI: 10.26911/the6thicph.04.19
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Satisfaction in Hospital

Abstract: Background: Quality of healthcare can be measured by observing its structure, its processes, and its outcomes. Patient satisfaction is an important measure of healthcare quality. Patient satisfaction is correlated with important outcomes, such as superior compliance, increased utilization of medical services, less malpractice litigation and better prognosis. This study aimed to examine determinants of patient satisfaction in hospital. Subjects and Method:A cross sectional study was carried out at 4 hospitals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This refers to their activities while living in Bali, which is the majority of trips compared to work. Sulistyo et al (2019) revealed that patients who did not work had higher satisfaction than patients who worked. This is because individuals who work generally have a habit of always focusing on the services, they should get to suit their needs.…”
Section: Differences In Patient Satisfaction Levels Based On Nationalitymentioning
confidence: 99%
See 4 more Smart Citations
“…This refers to their activities while living in Bali, which is the majority of trips compared to work. Sulistyo et al (2019) revealed that patients who did not work had higher satisfaction than patients who worked. This is because individuals who work generally have a habit of always focusing on the services, they should get to suit their needs.…”
Section: Differences In Patient Satisfaction Levels Based On Nationalitymentioning
confidence: 99%
“…This is because the service quality will positively influence patient satisfaction, i.e. the better service quality, the higher patients satisfaction (Sulistyo et al, 2019).…”
Section: Inpatient Satisfactions' Overviewmentioning
confidence: 99%
See 3 more Smart Citations